2015
DOI: 10.1016/j.ijms.2014.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Gas-phase reactions of a novel chemical ionization reagent, ClMn2+, with polar and nonpolar analytes in a linear quadrupole ion trap

Abstract: A chemical ionization reagent ion, ClMn 2 + , has been identified for the analysis of mixtures of organic compounds since it allows ionization of both polar and nonpolar analytes so that only one product ion, ClMn + adduct of the analyte, is generated without fragmentation. The reagent ion is formed upon ionization of ClMn(CO) 5 via corona discharge in an atmospheric pressure chemical ionization source of a linear quadrupole ion trap mass spectrometer. Volatile analytes were introduced into the ion trap via a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…2−6 Owing to a lack of ionizable functional groups, low basicity, or accompanying fragmentation, it is a challenging task to find an appropriate reagent ion that can react with alkanes to yield product ions characteristic of the original alkanes for the aim of chemical ionization mass spectrometry (CIMS) analysis. 7−9 In the search for proper reagent ions, the reactivity of bare or ligated transition metal ions, 10−14 such as Mn + , 15 CpCo + (Cp = cyclopentadienyl), 16−18 ClMn 2 + , 15 and ClMn(H 2 O) + , 19−21 toward alkanes has attracted increasing interest. Of considerable interest here are the gold cations Au + , which are typically quite reactive and have been paid much attention, since Wilkins's group found that Au + could react at thermal energies with a number of hydrocarbons and alcohols.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2−6 Owing to a lack of ionizable functional groups, low basicity, or accompanying fragmentation, it is a challenging task to find an appropriate reagent ion that can react with alkanes to yield product ions characteristic of the original alkanes for the aim of chemical ionization mass spectrometry (CIMS) analysis. 7−9 In the search for proper reagent ions, the reactivity of bare or ligated transition metal ions, 10−14 such as Mn + , 15 CpCo + (Cp = cyclopentadienyl), 16−18 ClMn 2 + , 15 and ClMn(H 2 O) + , 19−21 toward alkanes has attracted increasing interest. Of considerable interest here are the gold cations Au + , which are typically quite reactive and have been paid much attention, since Wilkins's group found that Au + could react at thermal energies with a number of hydrocarbons and alcohols.…”
Section: Introductionmentioning
confidence: 99%
“…In the search for proper reagent ions, the reactivity of bare or ligated transition metal ions, such as Mn + , CpCo + (Cp = cyclopentadienyl), ClMn 2 + , and ClMn­(H 2 O) + , toward alkanes has attracted increasing interest. Of considerable interest here are the gold cations Au + , which are typically quite reactive and have been paid much attention, since Wilkins’s group found that Au + could react at thermal energies with a number of hydrocarbons and alcohols. , Henceforth, the property and activity of the Au + ion have been the focus of research, such as extensive studies of gold cation complexation, the activity of Au + toward C 6 F 5 H, CH 3 X (X = F, Cl, Br, I), NO, NH 3 , and CS 2 , and endothermic activation of CH 4 , H 2 , O 2 , , and N 2 O .…”
Section: Introductionmentioning
confidence: 99%
“…However, they also have some shortcomings in the VOCs detection, such as no reactivity of NO + toward HCHO and severe fragmentation of large alkanes caused by O 2 + , CF 3 + , and CF 2 H + . To search for better reagent ions, there has been a renewal of interest in the gas-phase chemistry of bare or ligated transition metal ions, such as Au + , Mn + , CpCo + (Cp = cyclopentadienyl), ClMn 2 + , and ClMn­(H 2 O) + . It is noteworthy that gold cations Au + are typically quite reactive to many chemical molecules due to the strong relativistic effects. According to our recent exploratory study, Au + was potentially interesting and would be pursued as an appropriate reagent ion to ionize linear alkanes.…”
mentioning
confidence: 99%